2011
DOI: 10.1024/0301-1526/a000072
|View full text |Cite
|
Sign up to set email alerts
|

Successful surgical management of a recurrent leiomyosarcoma of the inferior vena cava

Abstract: The leiomyosarcoma of the inferior vena cava (IVC) is a rare malignant tumour of the venous system. The recurrence of the tumour after previous initial surgical resection is common and occurs in more than half of the patients. Surgical resection of a local recurrence is poorly described in the literature and the available data are restricted to a small number of cases. We report the case of a 62 year old woman, who was referred to our vascular surgical unit for recurrence of a leiomyosarcoma of the inferior ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Furthermore, complementary therapies, such as radio-and chemo-therapy often prove insufficient oncological control. The recurrence of the tumor after previous initial surgical resection is commonly diagnosed and occurs in the majority of the patients [36]. As a particularity, in our case, during a follow-up of four years, no recurrence of the tumor was identified, in comparison with other reported cases who underwent more than 20 surgical reinterventions after the primary surgery.…”
Section:  Discussionsupporting
confidence: 48%
“…Furthermore, complementary therapies, such as radio-and chemo-therapy often prove insufficient oncological control. The recurrence of the tumor after previous initial surgical resection is commonly diagnosed and occurs in the majority of the patients [36]. As a particularity, in our case, during a follow-up of four years, no recurrence of the tumor was identified, in comparison with other reported cases who underwent more than 20 surgical reinterventions after the primary surgery.…”
Section:  Discussionsupporting
confidence: 48%
“…In this data of 218 patients, radical resection was performed in 61.5 %, palliative resection in 11.9 %, and 26.6 % were inoperable [1,10]. Furthermore, Segment III tumours had an independent increased risk of death [12]. The second largest cohort evaluated was by Laskin et al in 2010, which concluded that complete surgical resection resulted in the best possibility of longterm survival; their study reported a 50 % 5 year survival [13].…”
Section: Discussionmentioning
confidence: 99%